Antibody titers against SARS-CoV-2 decline, but do not disappear for several months - Yamayoshi, S; Yasuhara, A; Ito, M; Akasaka, O; Nakamura, M; Nakachi, I; Koga, M; Mitamura, K; Yagi, K; Maeda, K; Kato, H; Nojima, M; et al. (Elsevier, 2021)
Background: To develop an effective vaccine against a novel viral pathogen, it is important to understand the longitudinal antibody responses against its first infection. Here we performed a longitudinal study of antibody responses against SARS-CoV-2 in symptomatic patients. Methods: Sequential blood samples were collected from 39 individuals at various timepoints between 0 and 154 days after onset. IgG or IgM titers to the receptor binding domain (RBD) of the S protein, the ectodomain of the S protein, and the N protein were determined by using an ELISA. Neutralizing antibody titers were measured by using a plaque reduction assay. Findings: The IgG titers to the RBD of the S protein, the ectodomain of the S protein, and the N protein peaked at about 20 days after onset, gradually decreased thereafter, and were maintained for several months after onset. Extrapolation modeling analysis suggested that the IgG antibodies were maintained for this amount of time because the rate of reduction slowed after 30 days post-onset. IgM titers to the RBD decreased rapidly and disappeared in some individuals after 90 days post-onset. All patients, except one, possessed neutralizing antibodies against authentic SARS-CoV-2, which they retained at 90 days after onset. The highest antibody titers in patients with severe infections were higher than those in patients with mild or moderate infections, but the decrease in antibody titer in the severe infection cohort was more remarkable than that in the mild or moderate infection cohort. Interpretation: Although the number of patients is limited, our results show that the antibody response against the first SARS-CoV-2 infection in symptomatic patients is typical of that observed in an acute viral infection.